Osteodystrophia Fibrosa in a Goat - A case report - Teswani, KJ; Pillai, Usha Narayna; N, Madhvan Unniy; Nair, Sudheesh S (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A nine month old male kid weighing 12 kg was presented to the University Veterinary Hospital, Mannuthy with a complaint of facial swelling for the past two months, reduced feed intake and loss of body condition. The animal was fed exclusively with concentrate feed consisting of bran, soyabean meal and coconut cake. On examination, the general appearance of animal was found abnormal puffy face and prominent eyeballs along with respiratory distress.The animal appeared dull and depressed, dehydrated with poor body condition. The gait was abnormal characterized by lameness and swollen joints. On clinical examination, mucous membranes were normal in colour, body temperature was102.2oF. On oral examination, symmetrical enlargement of face and jaws which were soft in texture and difficulty in opening the mouth was observed. The tongue was protruded outwards with frothy salivation. Routine laboratory examination of dung sample and blood smear were negative. Serum biochemistry revealed elevated (1420 IU/L) alkaline phosphatase (ALP), serum calcium and phosphorus were 7.6 mg/dl and 2.5 mg/dl respectively, serum protein, albumin and globulin were recorded 5.9 g/dl , 3.4 g/dl and 2.5 g/dl respectively. Radiograph of lateral and dorso-ventral view of skull indicated radiolucence of skull bones especially mandible
Keywords: Osteodystrophia; Fibrosa; goat